Acute Syphilitic Posterior Placoid Chorioretinitis With Subfoveal Choroidal Neovascularization Managed With Anti-VEGF Therapy. (May 2022) - Wai, Karen M.; Gong, Dan; Rodriguez, Marianeli; Cunningham Jr, Emmett T.; Vavvas, Demetrios G.; Eliott, Dean
Purpose: We describe the development and management of choroidal neovascularization (CNV) in a patient with acute syphilitic posterior placoid chorioretinitis (ASPPC). Methods: A retrospective case review is presented. Results: A 66-year-old man presented with unilateral blurry vision. He had a history of systemic syphilis infection twice, the last diagnosed 15 years before presentation and treated with intravenous ceftriaxone, resulting in seroreversion of an initially positive rapid plasma reagin (RPR). Examination revealed ASPPC with subfoveal CNV. Repeat testing revealed an RPR titer of 1:16 384. He was treated with 6 monthly intravitreal injections of bevacizumab and systemic antibiotics, resulting in resolution of his ASPPC and regression of his CNV. Conclusions: CNV is a rare complication of ASPPC. Multimodal imaging can be useful to suggest the diagnosis, and prompt treatment with systemic antibiotics and intravitreal anti-vascular endothelial growth factor agents can lead to resolution of ASPPC and regression of CNV, respectively.